Strategy Specifics of Multinational Companies Operating in Creative Industries - Shevchenko, Denys (2017)
The creative industry is a relatively new sector of the economy that grows rapidly and possesses huge potential. Multinational corporations have achieved a certain stage of development being highly globalized, vertically integrated and efficient. However, the problem of defining appropriate strategies and adjusting management approaches to industry's specifics arises. Therefore, the goal of this Diploma thesis is to analyze cultural industry market and to explain differences in business strategy between classical and cultural companies. In this academic work, the great part of attention will be devoted to a number of peculiarities. Among them firstly, the way of managing creative labor force that significantly differs from other industries. Secondly, risk management and level of intellectual property rights protection may either incentivize or discourage further development of creative products. The last but not the least, brand awareness exerts a significant impact on company's performance, therefore, analysis on this issue will be provided.